Public savings the effectiveness of sterilized foreign exchange intervention (2017)
"Even though there are theoretical models that support the effectiveness of sterilized Foreign Exchange Intervention (FXI) practiced by central banks uitll the objective of affecting the level and reducing the volatility of exchange rates cycle, empirical works provide mixed testimony for developed and emerging countries. The purpose of this paper is to offer empirical evidence for Colombia about how periods of public savings enhance the effectiveness of sterilized FXI by using a GARCH model. For doing so, it is first necessary to construct a measure of policy shocks finding out which are the determinants of foreign exchange (FX) purchases made by the Colombian Central Bank over the 2010-2014 period. During this time span the monetary authority used an innovative type of foreign exchange purchases known as the day to day pre-announced interventions for which a reaction function hasn't been built yet. This reaction function is estimated with an ordinary least squares (OLS) model". -- Tomado del resumen.